Psycho-social rehabilitation: income generation workshops in the context of mental health - Isabela Aparecida de Oliveira Lussi; Thelma Simões Matsukura; Michelle Selma Hahn (O Mundo da Saúde, 2011)
One of the great challenges for the intervention in mental health is the difficulty of access of users to a productive life. In spite of all the progresses, changes of paradigm and practices implemented destined to the psycho-social rehabilitation, inclusion in the world of work is still an important barrier to be challenged for reaching better levels of quality of life and more concrete conditions for social inclusion. This study aimed to identify the main exigencies, challenges, difficulties and opportunities considered by professionals who organize income generation workshops and/or cooperatives. From the location and mapping of existing practices in the State of Sao Paulo, we chose five experiences. Data collection used visits and interviews realized with professionals responsible by the workshops. The results have allowed the elaboration of a diagnosis that characterizes the experiences developed with the contextualized analysis. Discussion: although some experiences are making viable insertion realities, it is necessary to evaluate how much they must still be developed for promoting the autonomy and the development of citizenship of people involved.